De quelques héritages victoriens dans Ever After de Graham Swift (1992) - Isabelle Roblin (Revue LISA)
Published in 1992, Ever After is Graham Swift’s fifth novel. It is built around a Victorian metanarrative, the Notebooks written by Matthew Pearce, who is the ancestor of Bill Unwin, the main narrator. As with numerous re-writings of 19th century literary works (“retro-victorian” stories amongst others), Darwin’s and Lyell’s theories appear prominently in the novel. Matthew Pearce, an ardent reader of the naturalist and of the geologist, is going through a spiritual and family crisis and he recounts in his Notebooks his growing skepticism regarding the creationist religious dogma, of which his father-in-law, an Anglican minister, is a determined proponent. A few generations later, this crisis is reflected in his descendent Bill Unwin. Thus, in Ever After, the reader constantly goes to and fro between the Victorian and contemporary periods, the two narrators and their autobiographical texts. How do Matthew Pearce’s Notebooks resonate in the crisis his great-great-grandson is going through? How relevant is this Victorian heritage for a late 20th century narrator or for contemporary literature? I shall try and suggest a few leads to answer these questions.